Mapping ecological corridors in the Upper Paraguay River Basin, Brazil: Applications for sustainability, public policy and decision‐making - Maxwell daRosa Oliveira; Adriana Maria Espinoza Fernando; André Restel Camilo; Guellity Marcel Fonseca Pereira; Thaishi Leonardo daSilva; Walfrido Moraes Tomas (Conservation Science and Practice, 2025)
Abstract The Upper Paraguay Basin (BAP) is one of the largest river basins in South America, covering three countries: Brazil, Bolivia and Paraguay. In Brazil, one of the main risks to BAP conservation is the loss of native vegetation. In the floodplain region of the BAP, more than 13% of native vegetation was converted, while in the surrounding highlands the loss of native vegetation reached over 61% of the area. These values tend to increase, highlighting the importance of territorial planning for sustainable development in the region. In this sense, we mapped the ecological corridors in the Upper Paraguay Basin, in Brazil, to support conservation strategies focused on maintaining connectivity on a regional scale. To achieve this, we use the Least Cost Path and Circuitscape methods, based on a multispecies approach. As a result, we identified 303 fragments of native vegetation or conservation units that can be considered nodes and 859 ecological corridors. Of all the ecological corridors identified, around 288 were lost in just 3 years, due to the conversion of native vegetation. In general, our results were an extensive network of corridors, which can be applied in UPRB territorial planning, aiming to reduce the impacts of loss of connectivity in the region. Our results highlight the importance of territorial planning and quick and effective decision‐making to mitigate the effects of native vegetation loss for biodiversity conservation in the UPRB.